The politics and economics of regional integration in Africa: a comparative study of COMESA and SADC, 1980-2015 - Nagar, Dawn Isabel (My University, 2016)
This thesis examines the efforts of the Common Market for Eastern and Southern Africa (COMESA) and the Southern African Development Community (SADC) to promote regional integration between 1980 and 2015 in the areas of trade and security. The conceptual framework provides a focused review of general and specific literature on two key concepts of regional integration: divergence, and convergence. Throughout the thesis, the core focus is on the divergence and convergence of COMESA and SADC. The thesis articulates two analytical frameworks: the neoclassical economics approach, and the neoclassical realist approach. A historical account focuses on the history of the Preferential Trade Agreement (PTA) of 1981 that evolved into COMESA by 1993. A history of Southern Africa’s Frontline States (FLS), which evolved into the Southern African Development Coordination Conference (SADCC) in 1980, and later into SADC in 1992, is then provided. The thesis discusses apartheid South Africa’s involvement in the Eastern and Southern African regions. The thesis provides a discussion on the debate on the rationalisation processes of these two organisations: COMESA and SADC, between 1991 and 1997. The thesis next expands on the regionalisation processes of COMESA and SADC between 2008 and 2015. The main actors and factors assessed involve South Africa’s market-led regional approach, its regional developmental role and its economic impact on both regions since it joined SADC in 1994. The thesis expands on the two main regional integration approaches adopted by the COMESA–EAC (East African Community)–SADC Tripartite bloc (created in 2008) of variable geometry and trade liberalisation, as it moved towards its Tripartite Free Trade Area that was signed in June 2015. The thesis also provides definitions and assumptions of two new theories deployed to strengthen the research: i) neoclassical economic regional integration, and ii) neorealist security convergence, which are applied in the thesis. The thesis thus expands on how COMESA and SADC (as both institution and member states) manage multiple memberships. A central argument of the thesis is that multiple memberships have become a stumbling block for convergence. In furtherance of this argument, the thesis explains the benefits of regional integration schemes. Therefore assessed, is how developing countries are likely to be better served by “North–South” than by “South–South” free trade agreements. The analysis is expanded by a discussion of economic convergence in the neoclassical economic approach of open trade in regional trade agreements within the Southern African Customs Union (SACU) – whose five members all belong to SADC - with the presence of a regional hegemonic state: South Africa. To further expand the concept of regionalism to encompass security cooperation, the thesis finally assesses COMESA and SADC’s managing of regional security since the 2008 Tripartite Agreement, by employing the concept of regional security complexes.
Thesis (Ph.D. (International Relations))--University of the Witwatersrand, Faculty of Humanities, 2016
Keywords: Southern African Development Community; Common Market for Eastern and Southern Africa; Africa, Sub-Saharan--Foreign economic relations; Africa--Economic policy